Effectiveness of Smart City Policy Implementation in Improving the Quality of Public Services: Case Study in Denpasar City - I Wayan Sugiartana; Ni Made Citra Angreni; Aditya Manggala RS; Ni Made Puriati; I Nengah Merta (Business Management, 2026)
This study aims to evaluate the effectiveness of the implementation of smart city policies in improving public service quality in Denpasar. As a city that has adopted digital technology to enhance efficiency and sustainability, Denpasar focuses on utilizing the Internet of Things (IoT), digital twins, and digital platforms to improve public services. This research uses a descriptive qualitative approach with in-depth interviews and literature review to explore the perspectives of various stakeholders, both from the government and the community. The results show that although the smart city policy has had a positive impact on service efficiency in several sectors such as transportation and waste management, its implementation is still hindered by infrastructure issues, digital literacy among the public, and inter-sectoral coordination. Some of the main challenges faced include limited internet access and concerns over data security. This study recommends that the Denpasar government improve technology infrastructure, strengthen public digital literacy, and enhance cross-sector collaboration to maximize the potential of smart cities in improving public service quality.